STRATEGI PENGEMBANGAN DAN IMPLEMENTASI BUDAYA SEKOLAH DI SEKOLAH MENENGAH PERTAMA (SMP) MUHAMMADIYAH 1 DEPOK SLEMAN - Emma Nur Afriani (FAI UMY, 2016)

(untitled)
xvi ABSTRACT This research aims to know the development strategy of school culture, reviewing the implementation of school culture and analyze the obstacle factors and also the supporting factors in implementing the school culture in SMP Muhammadiyah 1 Depok Sleman. The type of this research was field research with descriptive qualitative characteristic. The informants of the research were the Head of Committee, the Headmaster, the Vice of Headmaster on Curriculum, the Vice of Headmaster on Public Relation, Facilities and Infrastructures, the Vice of Headmaster on Students and Staff of Students, 2 Counseling Teachers, the Head of Administration, and English Teacher. The data collecting technique were interview method, observation, and documentation. Then, the data were analyzed using qualitative data analysis of Miles and Huberman. The result of the research were; first, formulated the school culture values such as ethic, intellect, aesthetic, social and religion; also developed those values so that it could be guidance in strategy of school atmosphere development by developing the exemplary model, commitment, appreciation, motivation, cooperation, innovation and familial. Second, the implementation of school culture was realized using some activities such as (1) exemplary model: not being late, the 5s culture, pray together, the way dressing, and ceremony; (2) commitment: obey the rules, the teachers teach based on their competence, the responsibilities of teacher and student in doing their duties.; (3) appreciation: saying ‘thank you’ and giving reward; (4) cooperation: gotong royong (mutual assistance), helping and cooperating each others; (5) motivation: coaching, training, watching together, comparative study (studi banding) for teachers, the teachers’ service to students, prohibition in bringing hand phone, punishment, involving the students in active activities such as outdoor, outbound, live skill, extracurricular, camping and other things at school; (6) innovation: Ismubaris program, a fight against Holy Qur’an illiteracy, Jum’at krida, healthy, nutrient and culture; big day out and mini soccer, reflection of seven minute Islamic lecturing (kultum) and arba’in hadiths reading in Dzuhur pray, English club, reading culture, ulul albab and IT development; (7) familial: regular monthly meeting and annual meeting, camping, family gathering for teachers, communal Qur’an reading, live in reflection, and hospitality to society. Third, the obstacle factors in implementing school culture were the parents, the commitment of some teachers and staffs, the students, the facilities and infrastructures and also the environment society. The supporting factors were the human resources, the parties from out of school and the conducive school atmosphere. Key-Words: the development strategy, the implantation of school culture xvii ABSTRAK Penelitian ini bertujuan untuk mengetahui strategi pengembangan budaya sekolah, mengkaji implementasi budaya sekolah dan menganalisis faktor penghambat serta faktor pendukung dalam implementasi budaya sekolah di SMP Muhammadiyah 1 Depok Sleman. Jenis penelitian ini adalah penelitian lapangan bersifat kualitatif deskriptif. Narasumber penelitiannya yaitu Ketua Komite, Kepala Sekolah, Waka. Kurikulum, Waka. Humas dan Sarpras, Waka. Kesiswaan dan Staff Kesiswaan, 2 Guru Bimbingan Konseling, Kepala Staff Tata Usaha dan Guru Bahasa Inggris. Teknik pengumpulan data menggunakan metode wawancara, observasi, dan dokumentasi. Data yang diperoleh selanjutnya dianalisis menggunakan analisis data kualitatif menurut Miles dan Huberman. Hasil yang diperoleh dari penelitian ini yaitu pertama, merumuskan nilai-nilai budaya sekolah dalam hal ini adalah nilai etika, intelek, estetika, sosial dan agama; serta mengembangkan nilai-nilai tersebut sehingga menjadi panduan dalam strategi pengembangan iklim sekolah dengan mengembangkan keteladanan, komitmen, apresiasi, motivasi, kerjasama, inovasi dan kekeluargaan. Kedua, implementasi budaya sekolah direalisasikan dengan aktivitas dan kegiatan, seperti (1) keteladanan: tidak terlambat, budaya 5s, sholat berjama’ah, cara berpakaian, dan upacara; (2) komitmen: taat peraturan, guru mengajar sesuai dengan bidangnya, tanggung jawab guru dan siswa dalam menjalankan tugas; (3) apresiasi: ucapan terimakasih dan pemberian hadiah; (4) kerjasama: gotong royong, saling tolong menolong dan bekerjasama; (5) motivasi: pelatihan, training, nonton bersama dan study banding untuk guru, pelayanan guru terhadap siswa, larangan membawa handphone, pemberian hukuman, melibatkan siswa untuk aktif dalam kegiatan sekolah seperti out door, outbound, live skill, ekstrakurikuler dan mabit camp serta benda-benda di sekolah; (6) inovasi: program Ismubaris, pemberantasan buta huruf Al-Qur’an dan iqra’, Juma’t krida, sehat, gizi dan budaya; big day out dan mini soccer, pembiasaan kultum dan pembacaan hadist arba’in ketika sholat dzuhur, english club, budaya membaca, ulul albab dan pengembangan IT; (7) kekeluargaan: pertemuan rutin setiap bulan, setiap tahun, camping, family gathering untuk guru, pengajian bergilir, pengajian ortom, pembiasaan live in dan bersilaturahmi dengan masyarakat. Ketiga, faktor penghambat implementasi budaya sekolah ialah orang tua, komitmen beberapa guru dan karyawan, siswa, sarana dan prasarana serta lingkungan masyarakat. Faktor pendukungnya yaitu sumber daya manusia, pihak-pihak luar sekolah dan suasana sekolah yang kondusif. Key-Word: strategi pengembangan, implementasi budaya sekolah